DAMPAK ALIRAN MODAL ASING BAGI NEGARA-NEGARA BERKEMBANG: Proses âPerbaikanâ ataukah âPemburukanâ bagi Neraca Pembayaran - Purnomo, Didit (Universitas Muhammdaiyah Surakarta, 2002)
Generally, foreign capital invested in developing countries function as externally additional capital resources in order to accelerate investment and economical growth, and also to mobilize capital as well as to transform economical structure. In this article, the writer discusses many impacts as a logical consequence of foreign capital inflows in some developing countries, including low income countries. Here, much discussion is talking about pros and cons arguments related to foreign capital inflows. The writer views that the abundance of foreign capital inflows in some developing countries mostly brings to negative impacts (from the view of balance sheet). To support his argument, the writer also put a